THE USE OF GIS FOR THE MANAGEMENT OF NATURAL DISASTERS AND CRISIS SITUATIONS: THE USE OF GIS FOR THE MANAGEMENT OF NATURAL DISASTERS AND CRISIS SITUATIONS - Dimanova, Donika; Kuzmanov, Zdravko (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2025)
The increasing frequency and intensity of natural disasters highlight the urgent need for effective tools to support crisis management. Geographic Information Systems (GIS) have established themselves as a key platform for collecting, analyzing, and visualizing spatial data, providing decision-makers with timely and reliable information. This paper explores the role of GIS in disaster management across all critical phases: prevention, monitoring, response, and recovery. The study emphasizes the integration of real-time data, IoT sensors, and satellite imagery, which enhance early warning systems and improve coordination between institutions. In addition, technological innovations such as artificial intelligence, cloud computing, and AR/VR visualization extend the potential of GIS for predictive analytics, training, and rapid response. By examining international best practices and national applications, the paper outlines the challenges and opportunities for developing resilient GIS-based solutions. The findings demonstrate that GIS is not only a technological tool but also a strategic instrument for reducing risks, optimizing resource allocation, and supporting sustainable development in the face of natural disasters.